Pengaruh Pengetahuan, Sikap terhadap Pemenuhan Hak-hak Pasien dengan Motivasi sebagai Variabel Intervening pada Perawat Instalasi Rawat Inap di Rumah Sakit Umum Universitas Kristen Indonesia Jakarta - Sinaga, Friska Nathasia; Hutapea, Fresley; Pamungkas, Rian Adi (Jurnal Ners, 2024)
Fulfilling patient rights is one of the important things that is the main key in hospital services. In Indonesia, the fulfillment of these patient rights is legally regulated and the hospital must include these rights in the hospital regulations and explain them to the patient so that they understand their rights and obligations. This is a general consent that must be signed by the patient. However, in its implementation at RSU UKI Jakarta, most of the patients did not understand their rights and obligations. And there are still many nurses who do not understand general consent, and consider general consent to be the same as informed consent. This shows the lack of knowledge and awareness of nurses about the importance of fulfilling patient rights. The purpose of this study was to analyze the effect of knowledge, attitudes towards fulfilling patient rights, and motivation as intervening variables. This research is a quantitative approach with a saturated sample of 78 inpatient nurses at the hospital. This study uses the SEM-PLS method. The results show that knowledge has a positive and significant effect on motivation, attitude has a positive and significant effect on motivation, motivation has a significant positive effect on the behavior of fulfilling patient rights, knowledge has a positive and significant effect on the behavior of fulfilling patient rights, and attitude has a significant effect on behavior fulfillment of patient rights. Motivation as an intervening variable can mediate between attitudes and behavior in fulfilling patient rights, having a positive and significant influence. However, motivation does not mediate between knowledge and behavior in fulfilling patient rights, because it has been shown to have no significant effect. Keywords: knowledge, attitudes, motivation, fullfiling patient rights